PENGARUH PARAMETER PROSES TERHADAP KUAT TARIK SPESIMEN UJI ASTM D638 TYPE IV MENGGUNAKAN FILAMEN ESUN PLA+ - Wahyudi Hafizi Pratama; Hasdiansah Hasdiansah (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
FDM is one of the most frequently used methods in 3D Printing technology that is used to print filament products as material because this technique is easy to print 3D at a relatively low cost. Many researches on tensile testing have been carried out using PLA and ABS filaments, while for Esun PLA+ filaments are still rarely done. From these problems, it is necessary to research to get the effect of layer thickness and nozzle temperature to get the highest tensile strength value using Esub PLA+ filament. This research uses the Taguchi L25 OA method on the Anet 8 plus pro 3D Printing machine with dimensions of XYZ 300mm x 300mm x 350mm using a nozzle measuring 0.4 mm and using Esun PLA+ filament with a diameter of 1.75 mm. The process parameters in this research are Printing speed, nozzle temperature, layer thickness, cooling speed and orientation. The shape of the test specimen is in accordance with the ASTM d638 type IV standard. while to design the process parameters using L25 OA. Based on the results of this study, the highest tensile strength value with layer thickness (0.10mm) and nozzle temperature (2150C).